Uji Media Edukasi Tentang Pola Konsumsi Tablet Fe Untuk Mencegah Kejadian Resiko Tinggi Anemia Ibu Hamil - Restu Octasila; Reni Nofita; Siti Dariyani (Universitas Ngudi waluyo, 2020)
Background Pregnancy is a special condition for a woman as a prospective mother, because during pregnancy there will be many changes both physical, social and mental changes. During pregnancy there can also be things that cause a high-risk pregnancy especially those associated with anemia. This ignorance is one of the reasons for the lack of supporting media information related to the practice of how to consume FE tablets correctly. This study generally aims to analyze the level of understanding of mothers about how to consume FE tablets and compile an effective video information media for pregnant women about the practice of FE Tablet consumption patterns, so that it can effectively improve mothers' understanding of FE tablet consumption patterns practices that can meet FE's needs to you during pregnancy. In line with the objectives to be achieved in this study, this research uses the action research method. This method was chosen because in the first phase, research will be carried out on the condition and level of understanding of pregnant women regarding the practice of correct consumption patterns of FE tablets. Furthermore, in the second phase, an implementation / action will be carried out to implement and test the application and effectiveness of the use of information media in the form of video provided in Puskesmas Cisoka Kabupaten Tangerang. Research TKT at level 3. Results Increased knowledge of pregnant women before being given health education 42 to 65. Increased knowledge of pregnant women before being given video-based educational media 43 to 76. The targeted output in this study is to produce a video-based educational media that will increasing the percentage of regular consumption of Fe tablets in pregnant women can be accessed through inÂ https://www.youtube.com/watch?v=MIFi0y4KjCcÂ The conclusion in this study is the analys of media needed to increase the knowledge of pregnant women about the consumption patterns of Fe tablets that are adequate to reduce the risk of anemia in pregnant women. Significant increase in knowledge of pregnant women (P. value 0.001). The advice given to the providers of care (Midwives) is to use video-based educational media as an alternative media for health education.